Application of Employee Income Tax Planning And It’s Implication To Corporate Income Tax of PT. Pupuk Sriwidjaja Palembang - Indri Ariyanti; Zulkarnaini Zulkarnaini (EKSISTANSI, 2009)
The purpose of this research is to determine the practice of employee income Tax planning and its implication to corporate income tax of PT. Pupuk Sriwidjaja Palembang.  As the result of the corporate tax planning there have been a tax saving which its amount equal to Rp 7.124.809.000,- in year 2005, and equal to Rp 7.809.425.100,- in year 2006.  The corporate shouldn’t neglect the changes in applied income tax regulations, so the applied tax planning won’t violate the regulations.